Kekuatan Pembuktian Keterangan Terdakwa Dalam Tindak Pidana Perdagangan Anak - Ariska Widya Sari (Verstek, 2017)
This research aims to determine the strength of evidence of the defendants statements of who committed the child trafficking crime. The three defendants testified in the same trial. This is a normative law research or commonly called the doctrinal legal research done by researching library materials or secondary data consists of primary legal materials, secondary law and tertiary legal materials. Primary legal materials consist of legislation, notes the official records, the minutes in the making of legislation and the decision of the judge's decision.      As for the legal secondary material in the form of all the publication about the law which is not an official document. The results of the discussion describes efforts to prove that uses information from the defendant in the trial of the same in accordance with the provisions of the Indonesia Criminal Procedural code because out of information the defendant not found stuff to waive accountability criminal code of conduct well as a reason and the fact the judge thought that the defendant must be convicted and dropped criminal.      Keywords: Description defendant, Judge considerations, the Crime of Trafficking in Persons